IMPROVED KNOWLEDGE OF FIRST AID IN CHOKE - Riesmiyatiningdyah, Riesmiyatiningdyah; Nurinah Nurinah; Nadia Dhita Bela Santika; Eka Wahyuni Alviana; Agustina Mei Lerebulan; Winda Puspa Sari (Community Service Journal of Indonesia, 2019)
Health promotion activities about the first handling of choking in the Rangkah Kidul Elementary School, Sidoarjo is one form of community service in the form of counseling aimed at increasing children's knowledge about how to handle choking events which are events that often occur to cause death. The implementation of these activities on November 13, 2019 took place at the Rangkah Kidul Elementary School, Sidoarjo. The target is elementary students in Rangkah Kidul, Sidoarjo. Before the activity is carried out, there is a process of compiling the activity for approximately 3 weeks before the activity is carried out, starting from determining the theme of counseling to submitting permits to the parties concerned. As a form of evaluation, the activity was attended by 33 students and 1 teacher, participants participated in the activity happily and looked very enthusiastic, health promotion activities could run on time and smoothly. Keywords: Choke, first aid, health promotion.